Organizational Structure. (12th September 2016) - Ahmady, Gholam Ali; Mehrpour, Maryam; Nikooravesh, Aghdas
Abstract: Conceptualization of organizational structure is the manifestation of systematic thought. The organization is composed of elements, relations between elements and structure as a generality composing a unit. Structure is high combination of the relations between organizational elements forming existence philosophy of organizational activity. Systematic view of organization to structure shows that structure is composed of hard elements on one side and soft elements on the other side. The review of literature views structural relations from various aspects. Organizational structure is a way or method by which organizational activities are divided, organized and coordinated. The organizations created the structures to coordinate the activities of work factors and control the member performance. Organizational structure is shown in organizational chart. The present study is descriptive and library method is used for data collection.